Time transfer with BDS-3 signals: CV, PPP and IPPP. (1st April 2023) - Ren, Zhiling; Gong, Hang; Lyu, Daqian; Peng, Jing; Guo, Yu; Sun, Guangfu
Abstract: The third phase of BeiDou navigation satellite system (BDS-3) was officially commissioned on 31 July 2020. In this study, we make a comprehensive evaluation of BDS-3 time transfer with the B1I, B3I, B1C and B2a measurements. The multi-path (MP) errors and noises of different BDS-3 ranging signals are analyzed to illustrate characteristic of the code observations firstly. Then dual-frequency ionosphere-free linear combinations of BDS-3 B1I&B3I and B1C&B2a measurements are used to achieve time transfer. Using Multi-GNSS Experiment station observations, we evaluate the performance of BDS-3 time transfer with common-view (CV), precise point positioning (PPP) and integer ambiguity PPP (IPPP) techniques. Analysis results show that BDS-3 B1C&B2a CV time transfer links show a better performance than GPS L1P&L2P links, whereas BDS-3 B1I&B3I links are worse than GPS links. For the PPP time transfer, GPS links show the best performance, followed by BDS-3 B1C&B2a links and B1I&B3I links. Furthermore, frequency stability of BDS-3 IPPP time transfer is more stable than PPP solutions at the long average interval time. And the long-term frequency stability of BDS-3 IPPP is comparable with GPS IPPP.